The Impact of Climate Change on Potential Invasion Risk of Oryctes monoceros Worldwide - Aidoo, Owusu Fordjour; Hao, Mengmeng; Ding, Fangyu; Wang, Di; Jiang, Dong; Ma, Tian; Qian, Yushu; Tettey, Elizabeth; Yankey, Ndede; Dadzie Ninsin, Kodwo; Borgemeister, Christian (Frontiers in Ecology and Evolution, 2022)
As a significant threat to agriculture, pests have caused a great disservice to crop production and food security. Understanding the mechanisms of pests' outbreaks and invasion is critical in giving sound suggestions on their control and prevention strategies. The African rhinoceros beetle, Oryctes monoceros (Olivier), as the most damaging pest of palms, banana, sugarcane, and pineapple, severely threatens their production due to its ability to kill both young and matured hosts. Analyzing the effect of climate change on major parameters of O. monoceros life history has been an important issue recently, given its sensitivity to thermal conditions. However, information on how climate change alters geographical distribution of O. moncoeros is poorly understood. By combining environmental variables and occurrence records, we were able to assess environmental risk factors for O. monoceros and create risk maps for the pest using the Boosted Regression Tree (BRT) model. Our results significance of environmental variables showed that the annual temperature variation (39.45%), seasonality of temperature (23.00%), the isothermality (18.76%), precipitation of the hottest quarter months (6.07%), average variation of day time temperature (3.27%), were relatively important environmental factors that affected the distribution O. monoceros. We also found that the projected potential distributions of the pest’s habitats in all future global warming scenarios exceeded its present known distribution. The model predicts that habitat suitability for O. monoceros is predominantly concentrated along Africa's west and east coastlines, Asia's south coasts, South America's north and east coasts, and a few locations spread over North America's southern coasts and coastal regions. These outputs provide a solid theoretical foundation for O. monoceros risk evaluations and control.